MATHEMATICAL MODEL TO INVESTIGATE THE TEMPERATURE AND HARDNESS DISTRIBUTIONS DURING THE ANNEALING AND NORMALIZING TREATMENT (Journal of Engineering, 2010)
Annealing and normalizing treatment are one of the most important heat treatment for the steel and its alloys. In the present work a mathematical model has been used to simulate  this process, this model taken in account the variation in the physical material properties and heat transfer coefficient for the surface of metal. A numerical scheme based on control finite volume method has been used. A computer program with C++ language was constricted to found the final solution of the numerical equations.The model was used to estimate the temperatures distribution and the hardness value at each point of the workpiece. Good agreement has been obtained when compared the result of the present model with other experimental published data.